IDENTIFICATION OF BUSINESS CONSTRAINTS AND MARKETING OF POTATOES IN ACEH'S GAYO HIGHLANDS - Nurmala, Nurmala; Zahara, Hafni; Sullaida, Sullaida; Jamilah, Jamilah (RADJA PUBLIKA, 2021)
This study aims to identify the constraints on potato farming and marketing in the Gayo Highlands of Aceh. The research sample consisted of potato farmers and traders who were involved in potato marketing in Bener Meriah Regency. Determination of the sample of traders is done by snowball sampling technique. The identification of constraints uses a qualitative descriptive approach, while the income analysis uses an analysis of costs and farm revenues. The results showed that there were constraints in potato farming in the form of wilt disease which caused potatoes to be harvested immediately and the fruit produced was smaller. This will have an impact on decreasing the income of potato farming. The relatively high use of pesticides during the rainy season has implications for increasing the cost of potato farming, on the other hand the difficulty of accessing capital causes farmers to enter into potato farming partnerships with collector traders with the provision that potato marketing must be done to these traders. The development of potato farming in the Gayo Highlands of Aceh has encountered several obstacles including fluctuations in potato prices, lack of weed control which has implications for decreasing potato productivity, difficulty in accessing capital which will determine the sustainability of farming, income and farmers' welfare. farmers, namely selling potatoes through collectors, through wholesalers, and selling directly to consumers. Factors that determine farmers' decisions in marketing potatoes are the selling price, farm capital assistance, farm location, and potato quality. Direct marketing of potatoes (3rd type) to consumers is more efficient than other potato marketing channels because it can reduce farming and marketing costs. However this is rare and the sales volume of potatoes is very small.